Adjuvant therapy with GnRH agonists/tamoxifen in breast cancer should be a good council for patients with hormone receptor-positive tumours and wish to preserve fertility - Franco Junior, Jose Gonçalves [UNESP]; Oliveira, Joao Batista A [UNESP]; Petersen, Claudia G [UNESP]; Mauri, Ana L. [UNESP]; Baruffi, Ricardo LR [UNESP]; Cavagna, Mario [UNESP] (My University, 2011)
Infertility represents one of the main long-term consequences of combination chemotherapy used for the treatment of breast cancer. Approximately 60%-65% of breast cancers express the nuclear hormone receptor in premenopausal women. Adjuvant endocrine therapy is an integral component of care for patients with hormone receptor-positive (HR+) tumours. The GnRH agonist (GnRHa) alone or in combination with tamoxifen produces results at least similar to those obtained with the different chemotherapy protocols in patients with HR+ tumors with respect to recurrence-free survival and overall survival, Presentation of the hypothesis: It is time to indicate adjuvant therapy with GnRHa associated with tamoxifen for patients with breast cancer (HR+ tumours) if they want to preserve their reproductive function. Testing the hypothesis: Assessment of ovarian reserve tests: follicle stimulating hormone (FSH), anti-Mullerian hormone (AMH), inhibin B, antral follicle count (AFC) and ovarian volume 6 months, and 1 year after the end of therapy with GnRHa/tamoxifen. The recurrence-free survival and overall survival should be analysed. Implications of the hypothesis: The major implication will be to avoid adjuvant chemotherapy for patients with breast cancer (HR+ tumours) that request fertility preservation. It is expected that ovarian function should not be altered in almost all cases. © Todos os direitos reservados a SBRA - Sociedade Brasileira de Reprodução Assistida.
A terapêutica adjuvante com agonista do GnRH/tamoxifeno no cancer de mama pode ser um bom conselho para os pacientes com tumors receptor-hormonal positivos e desejo de preservar a fertilidade
Keywords: Adjuvant therapy; Breast cancer; Chemotherapy; Fertility preservation; GnRHa; Hormone receptor-positive; Tamoxifen; Cyclophosphamide; Fluorouracil; Follitropin; Gonadorelin agonist; Hormone receptor; Inhibin B; Methotrexate; Muellerian inhibiting factor; Tamoxifen; Adjuvant therapy; Amenorrhea; Breast cancer; Disease association; Disease free survival; Fertility; Human; Hypergonadotropism; Ovarian reserve; Ovary function; Ovary insufficiency; Overall survival; Reproduction